Critical Thinking Ability through Problem Based Learning in Social Studies Learning in Elementary School - Ropiah, Ropiah; Sapriya, Sapriya; Sopandi, Wahyu; Sujana, Atep (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2020)
The ability to think critically, problem to solve, communication and colaboration is a part of HOTS (High Order Thinking Skills) that students really need to possess as a preparation for facing global challenges. This study aims to determine differences in students' critical thinking skills in the experimental class that uses problem based learning and control class that use conventional approach. The research method used was a quasi-experimental design with nonequivalent control-group design. The research subjects are 40 students in class V of SDN 2 Kenanga. The experimental class of 20 students and the control class of 20 students. The instrument used was a test of critical thinking skills. Data processing techniques using the SPSS 23 software program. The results showed that there were differences in students' critical thinking abilities, the average critical thinking score of the experimental class students using problem based learning was higher than the control class with conventional approaches. So it can be concluded that social studies learning with problem based learning can improve students' critical thinking skills